2015
DOI: 10.1111/psyp.12567
|View full text |Cite
|
Sign up to set email alerts
|

N1 and P2 to words and wordlike stimuli in late elementary school children and adults

Abstract: In an investigation of the development of fine-tuning for word processing across the late elementary school years as indexed by the posterior N1 and P2 components of the event-related potential waveform, third, fourth, and fifth graders and a comparison group of adults viewed words, pseudowords, nonpronounceble letter strings, and false font strings in a semantic categorization task. In adults, N1 was larger to and P2 was later to words as compared to pseudowords, a finely tuned effect of lexicality reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 49 publications
4
39
1
Order By: Relevance
“…This seems to suggest that although early coarse print‐tuning development can be observed among young typically reading children, the full maturation of the N1 response to written words, which was tested using the current paradigm, takes much longer and happens in normal readers in adolescence, somewhere between the ages of 12 years, the age of the participants in this study, and 22 years, the age of the young adults in the study by van Setten et al (). This idea seems to be supported by the absence of a lexicality effect obtained with a word versus pseudoword contrast in children in contrast to adults (e.g., Coch & Meade, ). A question that can be raised on the basis of the current study is “when does N1 lateralization, as measured with a linguistic judgement task, shift from right to left?” It would be interesting to study this question in a study with normal reading participants of different ages between adolescence and young adulthood.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This seems to suggest that although early coarse print‐tuning development can be observed among young typically reading children, the full maturation of the N1 response to written words, which was tested using the current paradigm, takes much longer and happens in normal readers in adolescence, somewhere between the ages of 12 years, the age of the participants in this study, and 22 years, the age of the young adults in the study by van Setten et al (). This idea seems to be supported by the absence of a lexicality effect obtained with a word versus pseudoword contrast in children in contrast to adults (e.g., Coch & Meade, ). A question that can be raised on the basis of the current study is “when does N1 lateralization, as measured with a linguistic judgement task, shift from right to left?” It would be interesting to study this question in a study with normal reading participants of different ages between adolescence and young adulthood.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have found that the N1 is also sensitive to lexicality effects, as the N1 was found to be more negative in response to words in contrast to pseudowords. The development of this more fine‐grained tuning of the N1 to word‐specific characteristics seems to develop in adolescence as it was not found in late‐elementary school children, but it was present in adults (Coch & Meade, ). The lexicality effect was also not found in the study by Eberhard‐Moscicka et al () with first grade children nor in the studies by Araújo et al () and Kast et al () with preadolescent children.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the onset of reading instruction, normally developing children already are able to link sounds (phonology) with meaning (semantics; see review in Harm & Seidenberg, 2004); key components of what must be learned during reading instruction, then, are how to 1) represent orthography (e.g., how to recognize letters and distinguish between them) and 2) make linkages between the new orthographic representations and existing phonological and semantic representations (extensive review in Harm & Seidenberg, 2004). Of course, this cognitive development is accompanied by brain development, with functional brain organization changing during the course of reading instruction to support the new representations and linkages that are being acquired (see, for example, Coch & Meade, 2016;Maurer & McCandliss, 2007). One hallmark of the neural re-organization that accompanies reading acquisition is an increased left-lateralization for the higher visual processing of text (e.g, Maurer, Brem, Bucher, & Brandeis, 2005;McCandliss, Cohen, & Dehaene, 2003;Maurer, Blau, Yoncheva, & McCandliss, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, second graders showed a larger left hemisphere N170 to letters strings than symbol strings. In contrast, “fine-tuning” for print, reflected by sensitivity to regular orthographic structure (e.g., N170 response to words > pseudowords > consonant strings) appears to develop later, possibly not until after 5 th grade (Coch & Meade, 2016). …”
mentioning
confidence: 99%